The Manganese Influence on the AlSi12 Alloy Alfinal Bath Mechanical Properties Change - Hodinář, Lubomír; Svobodová, Jaroslava; Hren, Iryna; Cais, Jaromír; Michna, Štefan (Manufacturing Technology Journal, 2019)
The experiment described in this article deals with the possibility of AlSi12 alloy alfinal bath mechanical properties change used in the manufacture of the compression ignition engines pistons by the addition of manganese. The alfinal bath is intended for the aluminium layer deposition which provides more convenient connection of the carrier with the aluminum alloy after casting in the mold. The analysis performed in the experiment were focused on the assessment of the manganese addition influence in the form of the AlMn20 master alloy on the resulting mechanical properties of the AlSi12 alloy in which the iron content gradually changes (up to 7 wt. %). The iron is released from inserting cast iron rings. The research is primarily focused on assessing of strength and hardness of the alloy which is affected by the occurrence of intermetallic phases excluded in the microstructure depending on the ratio of iron to manganese content. The alloy with the high Fe content was subjected to the static tensile test and Brinell hardnes test measurement after the manganese addition.
Keywords: Alfinal Bath; Intermetallic Phase; Iron; Mangan; Strenght; Hardness